2018
DOI: 10.1021/acs.joc.7b03291
|View full text |Cite
|
Sign up to set email alerts
|

Cyanthiwigin Natural Product Core as a Complex Molecular Scaffold for Comparative Late-Stage C–H Functionalization Studies

Abstract: The desire for maximally efficient transformations in complex molecule synthesis has contributed to a surge of interest in C− H functionalization methods development in recent years. In contrast to the steady stream of methodological reports, however, there are noticeably fewer studies comparing the efficacies of different C−H functionalization protocols on a single structurally intricate substrate. Recognizing the importance of heteroatom incorporation in complex molecule synthesis, this report discloses a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 67 publications
1
10
0
2
Order By: Relevance
“…To this end, we treated tricycle 8 with DMDO at 0 °C, forming epoxide 17 in excellent yield as a single diastereomer (Scheme 4). As observed in our previous studies on the hydrogenation and C-H functionalization of the cyanthiwigin core, 20 oxygenation occurred selectively from the α-face of the molecule, likely due to steric shielding of the β-face by the methyl substituent at the B-C ring juncture. After unsuccessful attempts to open the epoxide under basic conditions (e.g., NaOH, LiEt 3 BH), we found that treatment of epoxide 17 with catalytic perchloric acid delievered the desired anti-diol (18) in excellent yield.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…To this end, we treated tricycle 8 with DMDO at 0 °C, forming epoxide 17 in excellent yield as a single diastereomer (Scheme 4). As observed in our previous studies on the hydrogenation and C-H functionalization of the cyanthiwigin core, 20 oxygenation occurred selectively from the α-face of the molecule, likely due to steric shielding of the β-face by the methyl substituent at the B-C ring juncture. After unsuccessful attempts to open the epoxide under basic conditions (e.g., NaOH, LiEt 3 BH), we found that treatment of epoxide 17 with catalytic perchloric acid delievered the desired anti-diol (18) in excellent yield.…”
Section: Resultssupporting
confidence: 72%
“…Available in 7 steps from succinic acid via a double enantioselective decarboxylative allylic alkylation strategy, 15,19 compound (-)-8 had previously been employed in a comparative study of latestage C-H functionalization (Scheme 1). 20 Along with allylic C-H oxidation of 8, various methods for 2° C-H chlorination and 3° C-H hydroxylation, amination, and azidation of hydrogenated tricycle 10 were compared. These efforts revealed reactivity patterns of the cyanthiwigin core and identified robust protocols for C-H oxidation of complex molecules.…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
“…For example, in a recent report on the diversification of the cyanthiwigin natural product class, Fe(PDP) and Fe(CF 3 -PDP) demonstrated divergent site-selectivities on the same tricyclic core. 102 It is significant to note that Fe(PDP) and Fe(CF 3 -PDP) are chiral catalysts and both the ( R,R ) and ( S,S ) versions should be evaluated, particularly in oxidations of rigid, chiral molecules. The diminished yields seen with ( S,S )-Fe(PDP) tertiary oxidation relative to ( R,R )-Fe(CF 3 -PDP) methylene oxidation of the cyanthiwigin core may be the result of a mismatch of the chirality of the Fe(PDP) catalyst with the chirality of the substrate.…”
Section: Altering Site-selectivities Via Catalyst Modifications: Fe(cmentioning
confidence: 99%
“…Recently, radical azidations, 88, 89 chlorinations 85b and metallonitrene aminations 95 have collectively shown the same site-selectivities on analogous substrates (Figure 25). 102 Recently, stoichiometric N -centered radicals reagents have been sterically tuned to alter site-selectivity in C—H chlorinations reactions (Figure 25A). 85c Current limitations of these reactions are that they proceed with low yields of C—H functionalized products, particularly at methylene sites, and free radical-based reactions ablate stereocenters at tertiary sites (Figure 25).…”
Section: Altering Site-selectivities Via Catalyst Modifications: Fe(cmentioning
confidence: 99%
“…Stoltz with coworkers developed late‐stage allylic C‐H acetoxylation of the tricyclic cyanthiwigin natural product core. [ 72 ] Only one synthetic protocol, relying on Pd(OAc) 2 catalyst and oxone as oxidant, allowed obtaining the acetoxylation product 104 in modest yield, while using Pd(OAc) 2 or palladium complexes with additional disulfoxide ligands with either O 2 or BQ as oxidants resulted in little or zero conversion of the tricyclic substrate 103 (Scheme 15). Interestingly, no acetoxylation was observed at the two CH 2 allylic positions in the cycloheptene ring.…”
Section: Transition Metal Catalyzed Acyloxylationsmentioning
confidence: 99%